Arabic Language Learning Strategy And The Problems Of Its Application At LKP Ibnu Khaldun Driyorejo Gresik - Sholihudin Al Ayubi (JOSSE: Journal of Social Science and Economics, 2022)
This article is the result of research that describes Arabic learning strategies and the problems faced by teachers. LKP Ibn Khaldun is an Arabic language development institution that uses multigames based on the "Smart Book of Memorizing Arabic-English Vocabulary for Children" in the form of mufradat themes and alternative language games along with the steps. This type of research is field research with a qualitative approach. Methods of collecting data with observation and documentation with data analysis techniques using descriptive qualitative. The learning strategies exemplified in this article are the practice of pointing at objects, the practice of matching paper with body parts, the practice of guessing the picture, and the practice of snowball throwing strategies. Based on the results of the study, one of the problems of learning strategies is the decreased interest of students in participating in the intensive learning process. Many of them actively participated in the learning at the beginning and never missed any meeting, but a few weeks later they did not attend again for various reasons. In addition, problematic in terms of abilities possessed, there are students who are intelligent and able to receive the material well, and vice versa.